NMR Characterization of Surface Receptor Protein Interactions in Live Cells Using Methylcellulose Hydrogels. (29th January 2020) - Mateos, Borja; Sealey‐Cardona, Marco; Balazs, Katja; Konrat, Judith; Staffler, Guenther; Konrat, Robert
Abstract: Interactions of transmembrane receptors with their extracellular ligands are essential for cellular communication and signaling and are therefore a major focus in drug discovery programs. The transition from in vitro to live cell interaction studies, however, is typically a bottleneck in many drug discovery projects due to the challenge of obtaining atomic‐resolution information under near‐physiological conditions. Although NMR spectroscopy is ideally suited to overcome this limitation, several experimental impairments are still present. Herein, we propose the use of methylcellulose hydrogels to study extracellular proteins and their interactions with plasma membrane receptors. This approach reduces cell sedimentation, prevents the internalization of membrane receptors, and increases cell survival, while retaining the free tumbling of extracellular proteins. Abstract : NMR‐Studien an Proteinen mit Lebendzellen benötigen eine sorgfältige Kontrolle der Zellintegrität und ‐lebensfähigkeit. Methylcellulose‐Hydrogele können genutzt werden, um die Bindung extrazellulärer Proteine an Zelloberflächenmembran‐Rezeptoren zu charakterisieren. Der Ansatz ist benutzerfreundlich, hat nützliche Eigenschaften zur Erhaltung von 3D‐Zellkulturen und schlägt eine Brücke zwischen In‐vitro‐ und In‐vivo‐Umgebungen in der Wirkstoffforschung.